Praxis Knowledge Mangement Dalam Kajian Manajemen Pendidikan Islam - Agryanda Agryanda; Moh Irwansyah; Lin Xinhong; Metly Elika Novebrian Rahayu (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This research explores information about Knowledge Management (KM) in education, especially in educational institutions. Using the Library Research method, the research objects used in this research include articles with the keywords KM in Education and KM. Comparative analysis of various articles is studied to produce a comprehensive exposition and conclusion of research results. The research results found that there are seven stages in KM. KM Cycle: acquire, use, learn, contribute, assess, maintain and release. The application of KM in educational institutions is important to build data registers and habits, focus on society's needs and fulfill them, organize work processes and information flows, and ensure technology availability to collect and share information, improve student learning and its results, and consider perspectives more comprehensively. Through this research, KM in education can receive more attention and development, especially in educational institutions.